2015
DOI: 10.1634/theoncologist.2014-0381
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Oral or Intravenous Ascorbate (Vitamin C) in Treating Patients With Cancer? A Systematic Review

Abstract: Background. Many cancer patients receive supplemental ascorbate (vitamin C) in the belief that it synergizes the anticancer effects of chemotherapy and reduces its toxicity. Methods. A systematic review was performed to evaluate the antitumor effects and toxicity of ascorbate treatment. Medline (1946 to March 2014), EMBASE (1947 to March 2014), and the Cochrane central register (1993 to March 2014) were searched for randomized and observational studies. Results. Of 696 identified records, 61 full‐text articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 65 publications
6
57
0
8
Order By: Relevance
“…A systematic review found no benefit of supplemental ascorbate (vitamin C) for overall or progression-free survival in cancer patients, most of whom had breast or colorectal cancer (Jacobs et al 2015). Another systematic review examined treatment efficacy and patient survival with the use of any adjuvant antioxidants during chemotherapy or radiotherapy (Yasueda et al 2016).…”
Section: Clinical Trials Of Antioxidants In Cancer Treatmentmentioning
confidence: 99%
“…A systematic review found no benefit of supplemental ascorbate (vitamin C) for overall or progression-free survival in cancer patients, most of whom had breast or colorectal cancer (Jacobs et al 2015). Another systematic review examined treatment efficacy and patient survival with the use of any adjuvant antioxidants during chemotherapy or radiotherapy (Yasueda et al 2016).…”
Section: Clinical Trials Of Antioxidants In Cancer Treatmentmentioning
confidence: 99%
“…Ascorbate plays a role in limiting inflammation, regulating cytokine production, and boosting the immune system [2][3][4][5][6][7][8]. It has a variety of properties that have generated interest in using it against cancer [9][10][11][12][13]: it enhances natural killer cell activity [14,15], increases collagen synthesis [16], inhibits capillary tubule formation (angiogenesis) [17,18], reduces inflammation in cancer patients [3], at millimolar concentrations, shows cytotoxicity against cancer cells [19][20][21][22][23][24] and the ability to reduce tumor growth in vivo [25][26][27][28][29][30][31][32][33][34]. Clinical trials to date [35][36][37][38][39][40] indicate that high dose (on the order of ten to 100 grams) intravenous ascorbate therapy can enhance anti-cancer effects of chemotherapy and improve quality of life in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Jacobs és mtsai a témában 1946 és 2014 között megjelent közlemények metaanalízisét végezték el, átte-kintésük alapján nem áll rendelkezésre elegendő bizonyí-ték, hogy a C-vitamin-pótlás segítené a kemoterápia hatékonyságát vagy csökkentené toxicitását daganatos betegekben [11].…”
Section: A C-vitamin Daganatellenes Hatásaunclassified